Removed: Facial Human Emotion Recognition by Using YOLO Faces Detection Algorithm - Hasan, Mustafa Asaad; Lazem, Ali Hussein; Alkhafaji, Mohamed Ayad (JOINCS (Journal of Informatics, Network, and Computer Science), 2023)
This article has been removed by the Editorial Office of the Journal of Informatics, Network, and Computer Science (JOINCS) following post-publication concerns relating to the submission process, authorship approval, and the integrity of the publication record. The information currently available to the journal indicates that the manuscript may not have proceeded through the journal’s standard author submission route. The Editorial Office also received subsequent communications disputing aspects of authorship and publication approval. In addition, the journal identified that an article under the same title had appeared in another journal, with a different authorship composition. Here is the URL: https://cajmtcs.casjournal.org/index.php/CAJMTCS/article/view/525 . In light of these unresolved concerns, the journal has removed the article from active publication to safeguard the integrity of the scholarly record while maintaining transparency for readers and institutions. We issue this notice without prejudice to any further factual clarification or additional editorial action that may be necessary. Editorial OfficeJournal of Informatics, Network, and Computer Science (JOINCS)Universitas Muhammadiyah Sidoarjo